Measuring Technology Readiness Index (TRI) of Management Information System Adoption in Higher Education - Nabila Rizky Oktadini; Jefven Fernando; Putri Eka Sevtiyuni; Muhammad Ali Buchari; Pacu Putra; Allsela Meiriza (Ultima InfoSys : Jurnal Ilmu Sistem Informasi, 2022)
The Laboratory of Software Engineering and Information Systems at Sriwijaya University is one of the services or learning media for students provided by Sriwijaya University. In order to support operational activities and good laboratory governance, a good management information system is needed. However, the adoption of new technology has some dificulties. It is necessary to know the level of readiness to accept new technology and one method to measure the level of readiness to accept new technology is the Technology Readiness Index (TRI). This research was conducted by distributing questionnaires to lecturers, structural laboratories and regular students of the 2018-2019 fasilkom. Data was processed using the Technology Readiness Index method by dividing the number of statements per variable by the variable weight. Then, the average total score for each statement is multiplied by the variable weight and the TRI value is obtained by adding up the scores of all variables. The results of this study found that the level of user readiness is included in High Technology Readiness with a score of 3.76. The Optimism value contributes the largest value to the total TRI value of the other variables, namely 1.010018. Then followed by Innovativeness of 0.986842, Discomfort of 0.917793 and Insecurity of 0.848009.